Analisis Terhadap Siswa Yang Berasal Dari Keluarga Broken Home (Studi KasusDi SMK Negeri 2 Gunung Talang) - Tumiyem, Tumiyem; Daharnis, Daharnis; Alizamar, Alizamar (Universitas Negeri Padang, 2015)
Brokenhomeisaconditionthat isnotharmoniousfamily. One reason for thebroken homebecause of adivorcebetweena husbandandwife.These conditionsaffecttheir children,such as lack ofaffection, do not getpropercareandacademicfailure.However,inthe field founda fewstudentswhohavehigh academicachievement.The purposeof thisstudyiscomparingthe factorsthatallow fordifferences inthe academicachievementof childrenwhocome froma broken home. The research was conductedinSMK 2Gunung Talang.The studyusedform of case studies. Capturingsubjectsin this studyusingpurposive sampling technique. Analysis ofthe datausingMilesandHubermaninteractive model.The conclusion ofthis studyisthedifference inacademicachievementexperienced bystudentsis causedby abroken home: (1) the relationshipwith their parents; students with high achievement have good relationship, students with low achievementhave not good enough in their relationship, (2) the relationshipwiththeirteachers; student with high achievement have good relationship, student low achievementhave not good enough in their relationship, (3)the relationshipwiththeir friends; students with high achievement have good relationship, students with low achievementhave not good enough in their relationship,(4) studentsattitude to themselves and family; student with high achievement have goodattitude with open behavior, students with low achievementhave introvert behavior,(5) ways of studentslearning; students with high achievement payfull attention on in learning and routine schedule, students with low achievement payless attention to the teachers explanationand routine in learning schedule.